Ideas have Consequences: A comparative Analysis of the transformative Role of ideas - Grimm, Christian (Momentum Quarterly, 2019)
Focus of this article is a discussion of the transformative role of ideas using the example of Friedrich August Hayek ́s hegemony theory for the implementation of a neoliberal dominated worldview. However, Hayek was not the only one, who believed in the power of ideas. Therefore, I discuss various forms of overlaps with other authors, namely Ludwig Mises, John M. Keynes, Walter Lippmann and Antonio Gramsci. The findings show, that these authors have developed quite similar theories in terms of intellectual supremacy, even though they come up from different political perspectives.
Keywords: Hegemony production; Neoliberalism; Hayek; Power of Ideas